Advanced Composite Materials: Properties and Applications - Bafekrpour, Ehsan (De Gruyter, 2017)
Composite materials are a major growth area within advanced materials and the range of applications for such products continues to grow and increase in diversity with every new development. Composite products are highly in demand and reached sales of $21.2 billion globally in 2014. The top three market segments in 2014 were transportation, construction, pipes, and tanks. Other segments include energy, automotive, and aerospace. This state-of-the-art book has been written by high-profile authors who have extensive experience and knowledge in the field of composite materials. The chapters in this collection would be useful for a wide range of audience: undergraduate and post-graduate students students, industrial professionals, materials scientists and researchers, and composite manufacturers. This book provides the reader with a wide range of information in the interdisciplinary subject area of composite materials. The book consists of thirteen chapters. It deals with two types of nanocomposites: graphene and carbon nanotube reinforced nanocomposites, their manufacturing, properties and applications. It also presents fibre reinforced composites and a comprehensive review of bio-composites. Furthurmore, it has a focus on thermal, mechanical and electrical properties of advanced composite materials.